2001
DOI: 10.1128/aem.67.4.1429-1436.2001
|View full text |Cite
|
Sign up to set email alerts
|

Use of Pulsed-Field Gel Electrophoresis and Flagellin Gene Typing in Identifying Clonal Groups of Campylobacter jejuni and Campylobacter coli in Farm and Clinical Environments

Abstract: Although campylobacters have been isolated from a wide range of animal hosts, the association between campylobacters isolated from humans and animals in the farm environment is unclear. We used flagellin gene typing and pulsed-field gel electrophoresis (PFGE) to investigate the genetic diversity among isolates from animals (cattle, sheep, and turkey) in farm environments and sporadic cases of campylobacteriosis in the same geographical area. Forty-eight combined fla types were seen among the 315 Campylobacter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
85
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(101 citation statements)
references
References 36 publications
15
85
1
Order By: Relevance
“…Twenty-one isolates (48.8%) belonged to individual genotypes. Earlier investigations also reported an extreme heterogeneity of C. jejuni isolated from cattle using stereotyping or varied methods of genotyping (Fitzgerald et al 2001, Nielsen 2002. The results of our study showed an extensive genomic diversity among C. jejuni strains isolated from animals belonging to single farms, most notably among C. jejuni isolated from farms using stanchion-barns.…”
Section: Methodssupporting
confidence: 60%
See 1 more Smart Citation
“…Twenty-one isolates (48.8%) belonged to individual genotypes. Earlier investigations also reported an extreme heterogeneity of C. jejuni isolated from cattle using stereotyping or varied methods of genotyping (Fitzgerald et al 2001, Nielsen 2002. The results of our study showed an extensive genomic diversity among C. jejuni strains isolated from animals belonging to single farms, most notably among C. jejuni isolated from farms using stanchion-barns.…”
Section: Methodssupporting
confidence: 60%
“…The results of our study showed an extensive genomic diversity among C. jejuni strains isolated from animals belonging to single farms, most notably among C. jejuni isolated from farms using stanchion-barns. Earlier investigations also reported the heterogeneity of C. jejuni isolated from cows belonging to a single farm (Fitzgerald et al 2001, Nielsen 2002. Such results indicate that cattle may have more exposure due to farming practices than chickens, where colonization is usually limited to one strain (Bull et al 2006).…”
Section: Methodsmentioning
confidence: 80%
“…Undercooked poultry meat, infected water and unpasteurized milk have been identified as risk factors of the infection (Fitzgerald et al, 2001;Devane et al, 2005). Campylobacter spp.…”
mentioning
confidence: 99%
“…Ideally, this method would be automated to achieve ' high throughput ' status. There are reports of instability in the flaA locus [41] but the majority of C. jejuni isolates are apparently genetically stable in this region over time [26,42,43] and that instability may be strain specific. Sequence-based methods such as MLST remove dependence on visual and potentially subjective, genotype assignment but require expensive equipment to handle medium to high numbers of isolates and reagents are costly [29,44].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a variety of methods have been used to compare animal and human isolates. Some studies have concluded that finding the same subtype in animal and human isolates is evidence of transmission from animals to humans or is evidence of a common source for animals and humans [17,[24][25][26][27][28]. However, the potential to identify genotypespecific risk factors for sporadic infection is yet to be evaluated.…”
Section: Introductionmentioning
confidence: 99%